Educational Leadership Styles, Secondary School Performance and Learner’s Achievement in Mauritius - RAMESH, VANI (International Journal of Psychosocial Rehabilitation, 2020)
The paper intends to understand the role of leadership management in the provision of Quality Education in Secondary Schools (Public and Private) in Mauritius. A model developed to test the significant relationship between the endowment of Quality Education in the Aided Private Secondary Schools, Public Secondary Schools, and the role of leadership management in Mauritius. Data collected from educators and the school leaders (rectors) working in 50 Private secondary schools and 46 state secondary schools. Structural Equation Modelling was adopted to test the set hypothesis for 404 (149 state secondary schools; 255 private secondary schools) respondents, including rectors, educators, administrative staff, and the Ministry (Public and Private). The outcome specified that Leadership is positively related to the impartment of quality education in the Mauritian secondary schools. Also, subordinates’ attitude towards their job enhances relational obligation among school leaders and educators, which in turn positively transmits to the development of job satisfaction and performances. Further, the leadership style of the school leaders may enhance the school performance and the learners’ achievement. Suggestions for theory and practice discussed in-depth, and directions for future research recommended.